Shallow Rupture Propagation of Pleistocene Earthquakes Along the Hurricane Fault, UT, Revealed by Hematite (U‐Th)/He Thermochronometry and Textures. Issue 17 (8th September 2021) - Taylor, Madison P.; Ault, Alexis K.; Odlum, Margaret L.; Newell, Dennis L.
Abstract: The material properties and distribution of faults above the seismogenic zone promote or inhibit earthquake rupture propagation. We document the depths and mechanics of fault slip along the seismically active Hurricane fault, UT, with scanning and transmission electron microscopy and hematite (U‐Th)/He thermochronometry. Hematite occurs as mm‐scale, striated patches on a >10 m 2 thin, mirror‐like silica fault surface. Hematite textures include bulbous aggregates and cataclasite, overlain by crystalline Fe‐oxide nanorods and an amorphous silica layer at the slip interface. Textures reflect mechanical, fluid, and heat‐assisted amorphization of hematite and silica‐rich host rock that weaken the fault and promote rupture propagation. Hematite (U‐Th)/He dates document episodes of mineralization and fault slip between 0.65 and 0.36 Ma at ∼300 m depth. Data illustrate that some earthquake ruptures repeatedly propagate along localized slip surfaces in the shallow crust and provide structural and material property constraints for in models of fault slip. Plain Language Summary: Earthquake ruptures can travel to the Earth's surface along discrete, large faults, or earthquake energy may be consumed in the shallow crust by the creation of small fault networks and fractured rock, which may reduce ground shaking intensity. Estimating earthquake hazards requires knowledge of subsurface material properties and how they change to promote or inhibit localized faulting. We investigate the Hurricane fault, UT, part of the Intermountain Seismic Belt or a north–south trending zone of recorded seismicity in the western US, which has the potential for large earthquakes (up to magnitude 7). We target hematite, an iron‐oxide mineral, on a mirror‐like, silica fault surface with microscopy and radiometric dating to document textural changes and the timing and depth of past fault slip. Nanoscale textures indicate the physical breakdown of hematite and surrounding rock, followed by the growth of new hematite and solidification of a silica surface layer, during an earthquake. Radioisotopic analyses capture hematite mineralization and fault slip 0.65–0.36 million years ago at shallow depths (∼300 m). In this example, the combination of mechanical and hydrothermal processes weaken fault materials, leading to repeated propagation of earthquake ruptures toward the surface along a discrete fault. Key Points: Hematite textures and (U‐Th)/He dates record mineralization and slip at ∼0.65–0.36 Ma and ∼300 m depth on the seismogenic Hurricane fault Comminution and hydrothermal fluids cause amorphization of hematite and adjacent host rock that weaken the fault during seismic slip Data demonstrate earthquake ruptures repeatedly propagate along localized slip surfaces in the shallow crust